The Mawar Emas Program for Fighting Moneylenders - Jamaliah Said; Muhammad Azizurrohman; Riduan Mas'ud (Shirkah: Journal of Economics and Business, 2023)
The Mawar Emas Program, a program aimed at countering moneylenders in West Nusa Tenggara, Indonesia, has been running for two years. However, there is insufficient research to evaluate its effectiveness, requiring further analysis. This qualitative study evaluates the performance of this program since its establishment. The study's respondents were mosque administrators, the Chair and Secretary of the NTB Sharia Economic Community (MES), beneficiaries, and banks. Each respondent was interviewed to collect data related to the Mawar Emas program. The study found that the program has aided 32 mosques in West Nusa Tenggara, benefiting a total of 1,194 potential borrowers. The Mawar Emas program has an annual budget of Rp. 1,275,000,000; however, these funds have not been fully utilized. Funding and absorption of funds decreased in the program's second year. Several program elements require evaluation, such as increased funding, default rates, training delivery, obsolete data, and profit-oriented institutions. The study's findings contribute to facilitating MES's ability to assess and improve the program.